(3HQhJhchd dHfGfs - (3YHO GdQMef YOQIs
(3ChdgG (B:s
(3Gf OQGSI GdeMGOKGJ MUhdgG hJWhQgG heGQGabgG ef GdCYjH SjGSjI hfJL YfgG ef EQSGd bhi YScQjI s
(3BNQgG (B:s
(3GeG JQcjG ade JQ HGdHQhJhchd GdEeXgQkG ef eXGgQ GdfVGd GdGhQhHi dGJHJdGYgG gPG eG NU GdYgO GdChd QGLjkG Cf Cchf habJ dJUhjQ hGbYg GdJGQjNi hGdSdGe s
(3HBNQgG bGFeI HGdeUGOQ hGdeQGLYs
(3HChdg agQSs
(3cJH HBdg cGJHI hgh YHGQI Yf QSGdI LGeYjI s
Keywords: (3GdSjGSI hGdGLJeGYs